The Paradigm of Constructivist Philosophy as an Epistemological Foundation Formation of Meaning in Arabic Language Learning - Mu Ida Nur Fadhilah; Istiada (JEICI - Journal of Education and Islamic Contemporary Issue, 2025)
This article discusses constructivism as an epistemological foundation in the formation of meaning in Arabic language learning. The main problem raised is how constructivism explains the process of knowledge construction and how the paradigm is implemented in the pedagogical context of the Arabic language. This research employs a library research method, analysing primary and secondary sources, including philosophy books, epistemological studies, and recent journal articles on constructivism and Arabic language learning. The survey results indicate that constructivism provides a robust theoretical framework for understanding how learners construct meaning through learning experiences, social interaction, and reflection. The application of this approach has been shown to improve students' linguistic and communicative abilities through authentic assignments, collaborative activities, and contextual learning designs. However, its implementation still faces several challenges, including teacher readiness, limited facilities, and an evaluation system that is not aligned with constructivist principles. This article emphasises the need to strengthen teachers' pedagogical competence, provide a supportive learning environment, and adapt the curriculum to make learning Arabic more meaningful and relevant to students' needs.